Phytochemical and Antimicrobial Activity of Selected Microorganism of Bark Extract of the Plant Crataeva religiosa - Gowsalya, P (International Journal of Pharmaceutical & Biological Archive, 2013)
Phytochemical and Antimicrobial Activity of Selected Microorganism of Bark Extract of the Plant Crataeva religiosa